2020
DOI: 10.1177/0300060520925660
|View full text |Cite
|
Sign up to set email alerts
|

Combining interferon-γrelease assays with lymphocyte enumeration for diagnosis ofMycobacterium tuberculosisinfection

Abstract: Objective To investigate the possibility of combining tuberculosis (TB)-interferon (IFN)-γ release assays (IGRAs) with lymphocyte enumeration for diagnosis of Mycobacterium tuberculosis infection. Methods We performed a retrospective study of 166 TB patients [68 patients with pulmonary tuberculosis TB (PTB) and 98 patients with extra-pulmonary TB (EPTB)] diagnosed in our hospital between January 2016 and May 2018 along with 377 non-TB patients. The diagnostic performance of the TB-IGRA was evaluated using rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The corresponding ROC curve was plotted to evaluate the accuracy of the assay with respect to the serodiagnosis. An AUC of 0.91 was calculated (IC 95% 0.82-0.99) which is similar to or exceeds that reported for ELISPOT-based diagnostic tests [16,17,24] or other IFN-γ release assays (IGRA)-based diagnostic tests [25][26][27]. In addition, subsequent evaluation of IFN-γ, IL-2, IL-12 and IL-17 from among 17 donors showed, for the first time to our knowledge, a greater stimulation of toxo+ compared with toxo-subjects, confirming that this stimulation approach elicited a specific Th1/Th17 immune response.…”
Section: Plos Onesupporting
confidence: 62%
“…The corresponding ROC curve was plotted to evaluate the accuracy of the assay with respect to the serodiagnosis. An AUC of 0.91 was calculated (IC 95% 0.82-0.99) which is similar to or exceeds that reported for ELISPOT-based diagnostic tests [16,17,24] or other IFN-γ release assays (IGRA)-based diagnostic tests [25][26][27]. In addition, subsequent evaluation of IFN-γ, IL-2, IL-12 and IL-17 from among 17 donors showed, for the first time to our knowledge, a greater stimulation of toxo+ compared with toxo-subjects, confirming that this stimulation approach elicited a specific Th1/Th17 immune response.…”
Section: Plos Onesupporting
confidence: 62%
“…The study by Lv et al. found that the lymphocytes of non-TB were 1.48 ± 0.05, that of pulmonary TB was 1.31 ± 0.08, and that of extrapulmonary TB was 1.23 ± 0.06 ( 18 ). The number of lymphocytes in non-TB was significantly decreased, and the comparison was statistically significant(P=0.004).…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the mean of the duplicates was calculated for N, S1-, and S2-stimulated samples, and control values (N) were subtracted from Ag-stimulated values (S1/S2). Since the literature reports a baseline circulating plasma IFN-γ concentration of around <20 pg/mL in healthy individuals, a positive T cell response was defined as an IFN-γ release >20 pg/mL [ 19 , 20 ]. Research concerning concentration thresholds for the other cytokines above which the T cell response would be considered positive was very scarce.…”
Section: Methodsmentioning
confidence: 99%